Epidemiology of HIV Infection and Molecular and Genetic Features of the Virus at the Infected Persons in Siberian Federal District - A. N. Kolomeets; G. A. Kalacheva; L. I. Levakhina; V. K. Yastrebov; A. Kh. Nurpeysova; I. V. Yarusova (Эпидемиология и вакцинопрофилактика)
Relevance. HIV infection epidemic in the Siberian Federal District (SFD) continues to develop with a tendency to incidence growth. The prevalence indicator in the district on 1/1/2015 made 948,4 on 100 thousand of the population. Since 1996 within 20 years in Siberian federal district the group which is the most affected with HIV infection were the consumers of injecting drugs (CID). The greatest number of patients with HIV is registered among males from risk groups in age group of 30 - 39 years (25.8%). And the combined infections lead risky behavior in respect of HIV infection to increase in number of the dead. Goal. Studied the frequency distribution of mutations associated with resistance of human immunodeficiency virus to three main classes of antiretrovirals in patients on therapy, as well as «naive» patients Materials and methods. The study is supposed to monitor the epidemic process of HIV infection in the Siberian Federal District in 2001 - 2015. Results. Patients on therapy, noted the prevalence of mutations of HIV to nucleoside and nonnucleoside reverse transcriptase inhibitors. The "naive" patients in the majority of cases revealed no mutations associated with resistance. Conclusions. Established the dominance of HIV subtype A1, along with a significant proportion of circulating recombinant form 02_AG and 63_02А1.